PENGARUH STRUKTUR ASET, PERTUMBUHAN PENJUALAN, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Aprilla, Dwi Intan; Limba, Franco Benony (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2024)
The aim of this research is to empirically test the effect of asset structure, sales growth and firm size on the capital structure of pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This research uses quantitative methods by analyzing data using multiple linear regression analysis. The population used in this research was 11 companies with 4 years period of research and the sample used was 43 samples selected using purposive sampling techniques. The results of this research show that asset structure and sales growth have a positive and significant effect on capital structure, while company size has no ieffect on capital structure.